2022
DOI: 10.1002/hsr2.831
|View full text |Cite|
|
Sign up to set email alerts
|

An assessment of publishing practices and barriers faced by medical students to conduct research: A cross‐sectional study from Pakistan

Abstract: Background Pakistan being a low‐ and middle‐income country, its institutes are substantially deficient in scientific and technological aspects and share limited research contributions to the world repositories. Therefore, there is a rising concern to reflect on the history and status of publishing attitudes among medical students in Pakistan and to highlight and address the barriers that they are facing. Methods A study was conducted aiming to determine the experience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A recent study in Saudi Arabia similarly reported that support from supervisors was a key factor in achieving the publication of a paper. 8 Studies from other regions identify various factors such as lack of training in writing and seniors’ attitudes 9 , 10 −…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Saudi Arabia similarly reported that support from supervisors was a key factor in achieving the publication of a paper. 8 Studies from other regions identify various factors such as lack of training in writing and seniors’ attitudes 9 , 10 −…”
Section: Discussionmentioning
confidence: 99%
“…were over four times more likely to successfully publish a manuscript than those who answered "no." 48 Data describing interventions to improve medical writing skills are limited. In one report, nine papers were published by 8 of 18 pharmacy residents in the 4 years before initiation of a writing development program.…”
Section: Writing Skillsmentioning
confidence: 99%
“…In one study of 54 family medicine residents, over 50% rated “lack of medical writing skills” as an important barrier to conducting high‐quality research 47 . Another survey of 1225 medical residents found that those who answered “yes” to the question “Have you been taught how to write a paper?” were over four times more likely to successfully publish a manuscript than those who answered “no.” 48 …”
Section: Research Readinessmentioning
confidence: 99%
“…Understanding the manuscript submission process is crucial, as research indicates that students who are familiar with it are more likely to have their articles published than those who are not. 9 However, novice researchers often lack such knowledge because of insufficient educational opportunities related to research. Having a mentor or a colleague who can provide guidance and advice is particularly important, 10,11 but clinical physicians may not always have access to experienced mentors.…”
mentioning
confidence: 99%